Después del manicomio - Villa-Palomino, Julio (2024)
This article explores Peru’s transition towards community mental health from 1980 to 2022. Using an approach from medical anthropology and related social sciences, we argue that the community mental health reform in Peru has been influenced and shaped by multiple sociohistorical and political processes such as the period of internal armed conflict, economic crises, and the adoption of neoliberal policies. This article is based on an analysis of the national guidelines and reports related to mental health, participant observation in a Community Mental Health Center and with residents of a district of Lima, and interviews with citizens, health providers, and mental health activists. The analysis of the national mental health guidelines shows how sociohistorical processes influence mental health policies. The ethnographic work complicates citizens’ varying perceptions of the community mental health model and the process of psychiatric deinstitutionalization. Now that mental health care takes place in the community, our ethnographic analysis points to changes in different notions of madness, care, and mental health and illness. The mental health reform also generates opportunities, such as mental health activism and the potential inclusion of community actors, as well as the inclusion of people with mental health problems in the elaboration of their diagnoses and treatments.